PENGARUH KUALITAS PELAYANAN, PRODUK, HARGA DAN LOKASI TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA UD. EVA GROUP MATARAM - Rahmadani, Fitri; Suardana, I Made; Samudra, Hengki (Sekolah Tinggi Ilmu Ekonomi AMM Mataram, 2019)
This study aims to determine the satisfaction is an intervening variable there is a relationship between service quality variable, product varieble, price varieble and location to loyalty varieble in UD. Eva Group Mataram. The population in this study is all consumers who become customers at UD. Eva Group whose number is unidentified. Sampling technique used with purposive sampling method. Data were obtained from questionnaires distribution with total sample of 100 people. Methods of data collection using questionnaire method and data analysis method using path analysis. Based on the results of data analysis, it can be concluded as follows: 1) customer satisfaction is an intervening variable on the relationship variable between service quality variable and customer loyalty variable, 2) Customer satisfaction is the intervening variable on the relationship variable between the product with customer loyalty variable, 3) Is an intervening variable on the relationship between price and customer loyalty, 4) Customer satisfaction is an intervening variable on the relationship between location and customer loyalty